Exploring University Students’ Experiences of English Learning through Duolingo - Ayu Andira; Hariadi Syam; Alifiah Pratiwi; Ray Suryadi; Rais Abin (Universitas Islam Negeri Palopo, 2025)
This study explores university students’ experiences of learning English through the Duolingo application. Employing a qualitative descriptive design, the research involved 15 English education students at Universitas Sembilanbelas November Kolaka over a six-week data collection period. Data were gathered through semi-structured interviews and classroom observations, and then analyzed thematically using Braun and Clarke’s (2006) six-phase approach, guided by a constructivist learning framework. The analysis identified students’ perceptions, perceived benefits, and challenges in using Duolingo as a language learning tool. Findings revealed that Duolingo enhanced students’ vocabulary acquisition, learning motivation, and autonomous study habits. However, participants also reported limitations such as repetitive exercises, insufficient opportunities for communicative speaking practice, and reliance on internet connectivity. Results indicate that while Duolingo can effectively supplement English learning, it is most beneficial when integrated with classroom-based instruction and teacher guidance. Overall, the study underscores the importance of combining digital learning applications with formal educational contexts to maximize language development and learner engagement.